Hak Pentingnya Pendidikan Kewarganegaraan Bagi Generasi Muda - Eli Sabrifha; Elsa Miranti (Jurnal Sains, Teknik, Ekonomi, dan Pendidikan, 2026)
Civic Education has an important role in shaping the character of the younger generation to develop national awareness and responsibility as citizens. In the era of globalization, young people face various challenges such as declining nationalism, the influence of foreign cultures, and a lack of concern for democratic and social values. This paper aims to explain the importance of Civic Education for the younger generation in building patriotism, social responsibility, and active participation in social and national life. The method used in writing this paper is a literature study method by collecting various sources such as books, journals, and scientific articles relevant to the topic discussed. The discussion results show that Civic Education can serve as a means of character building, instilling moral values, and increasing legal and democratic awareness among the younger generation so that they can become intelligent, active, and responsible citizens.